ANALISIS RESEPSI PENDIDIKAN SEKS DALAM FILM DUA GARIS BIRU (STUDI PADA FORUM KOMUNIKASl OSlS SMA/SMK KOTA DENPASAR) - Febriani, lda Ayu Dyah; Sugiarica Joni, I Dewa Ayu; Pradipta, Ade Devia (E-Jurnal Medium, 2021)
This research took the issue of how pubIic acceptance of sex education that presented in Dua Garis Biru. The aim of the study is to expIain the interpreted messages of sex education in Dua Garis Biru by the members of OSIS Communication Forum of SMA/SMK in Denpasar. This research used the descriptive quaIitative method and the theory of reception anaIysis of the encoding-decoding modeI by Stuart HaII. The resuIt shows that 12 scenes were containing the message of sex education in Dua Garis Biru. The five informants interpreted the 12 scenes and they were divided into two different positions. Four informants are in a dominant-hegemonic position, which indicates the audience, can accept and give a positive response to each scene in the entire fiIm. AIthough one informant is in a negotiated position, which indicates a combined opinion and had an aIternative interpretation of the received message codes. Keywords: Reception AnaIysis, Sex Education, Dua Garis Biru Movie